Ensuring food availability in the household: evidences from rural area of North-East Malaysia - Afandi, Aflah; ., Wan A. Manan; AM, Noorizam; HB, Syahrul; ZAMH, Zabidi-Hussin (2006)
Household food insecurity is increasingly being recognised as a serious public health concern in Malaysia. While starvation seldom occurs in this country, children and adultsdo go hungry andchronic mildundernutrition occurs when financialresources are low. The problem of food insecurity can be broadly defined as limited, inadequate or insecure access by individuals and households to sufficient, safe, nutritious and personally acceptable foods to meet their dietary requirements for a healthy life. The aim of this study was to investigate the relationship between food insecurity and nutritional outcome among preschool children in a rural district and examine how low-income families meet their food and nutrition needs. In this cross-sectional study, weight and height / length were measured in a sample of mothers and children from 296 selected households. Questionnaires were used to collect socio-economic and other related information. The validated Radimer / Cornell Food Insecurity instrument was utilised to assess food security. Hunger and food insecurity was reported by 54% (n=159) of the mothers surveyed, which include 21% (n=62) individual (mother) food insecure and 21% (n=62) child hunger. Among food insecure households with children; 70.4% reported that at times they could not afford to feed their children with balanced meals, 35.2% of the children were not eating enough and 34.6% of the children reported ever getting hungry as the family could not afford to provide enough food. This study also revealed that the mothersplayprime roles in ensuring foodsecurity andnutrition status oftheir household members by practising some coping strategies. Although foods were spared for the children, the quality of the food is insufficient to meet the recommended needs. This study suggests that food insecurity is one possible reason that may contribute to poor growth and development of young children in the study area.